2020
DOI: 10.1088/1742-6596/1700/1/012092
|View full text |Cite
|
Sign up to set email alerts
|

Vocational skills learning model strategies during covid-19

Abstract: The focus of this research is the skills learning model used by teachers, especially those who teach practical subjects. In accordance with the purpose of vocational education which says that graduates from vocational high schools are graduates who are ready to work in the industrial and business world. The purpose of this study is to describe the skills learning model strategy used by teachers when Covid-19 hit Indonesia. The research method used is a qualitative research method with a descriptive approach. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Nevertheless, this result is different from Orabi et al (2020), which state that "there is a significant relationship between vocational life skills and learning achievement," while Starkey (2020) states that "teachers place more emphasis on developing vocational skills." According to the results as well as the opinions of experts, it can be concluded that vocational life skills are one of the determinants of student learning outcomes since students who have high vocational life skills will find it easier to complete a worksheet with satisfactory results for the students who have high vocational skills compared to lack of vocational skills (Kholifah et al, 2020), so that the vocational life skills possessed by 6th-grade Madrasah Ibtidaiyah Muhammadiyah Jragan students is good, and has a significant relationship to the learning outcomes.…”
Section: The Influence Of Vocational Skills On Learning Outcomesmentioning
confidence: 99%
“…Nevertheless, this result is different from Orabi et al (2020), which state that "there is a significant relationship between vocational life skills and learning achievement," while Starkey (2020) states that "teachers place more emphasis on developing vocational skills." According to the results as well as the opinions of experts, it can be concluded that vocational life skills are one of the determinants of student learning outcomes since students who have high vocational life skills will find it easier to complete a worksheet with satisfactory results for the students who have high vocational skills compared to lack of vocational skills (Kholifah et al, 2020), so that the vocational life skills possessed by 6th-grade Madrasah Ibtidaiyah Muhammadiyah Jragan students is good, and has a significant relationship to the learning outcomes.…”
Section: The Influence Of Vocational Skills On Learning Outcomesmentioning
confidence: 99%
“…Sundarasen et al (2020) revealed that 17 to 18 years old group students are more anxious which should be given priority by the educational institution. Vocational schools provide practical and contextual meaningful learning in regards to values of daily life to enhance students' capability and skills for survival and development (Kholifah et al, 2020), thus, carrying out online learning will be more challenging. Finally, addressing the above-mentioned issues, the present study proposes the following research questions: a) How are the features of the vocational high school students' emotional experiences in the learning of English during the Covid-19 pandemic?…”
Section: Introductionmentioning
confidence: 99%
“…Based on education level, the highest open unemployment rate is in secondary education (SMA and SMK), which is 9.72 percent. On the other hand, the COVID-19 pandemic has disrupted economic activity, uncertainty, and 6.4 million workers were forced to be laid off (Hidayatullah et al, 2020;Thomas, 2020;Casady & Baxter, 2020;Amalia, 2020;Kholifah et al, 2020) stated that the COVID-19 pandemic had put quite intense pressure on companies that have never been faced before, even partnerships that have caused project failures and resulted in many companies laying off their work relationships. As a result, the economic sector also increases the number of closed components (Bauer & Weber, 2020;Rizal, 2020;Alon et al, 2020).…”
Section: Introductionmentioning
confidence: 99%